USE OF HIGH RESOLUTION SATELLITE DATA (IKONOS IMAGERY) FOR LOGISTIC SUPPORT - Tri Muji Susantoro; Adji Gatot Tjiptono; Suliantara Suliantara (Scientific Contributions Oil and Gas, 2005)
Many activities must be done before doing the 3D seismic survey. 3D seismic work needs accurate and precise information to minimize the cost and negative impact, and or dispute with the local people. The data needs information on road for moving instrument, bridge, river and Ancient River. Data of landuse and landcover, building, public facility, demographic and administration are required for estimating compensation. The use of remote sensing is a good alternative to achieve this objective. The 3D seismic survey will involve an amount of labors in the fields where the survey is conducted. During the survey a number of equipments will be planted and connected by wire. Therefore, the seismic survey will directly make contracts with local people and theirs proprietaries for temporary use or damage compensation. 3D seismic survey can be classified as a complex activities, apart from a large number of labors that are needed to carry explosive and equipments which will be used to comply the survey, social problem must be solved first. Especially when the study area is conducted in a well developed area with dense population, cultivation and other utilities. Considering the previous facts, a well plan operation in the office that is supported by detail and up to date surface map is actually needed. High accuracy and up to date surface map was considered as a critical basic information for the 3D seismic planning. Remote sensing technology with the high spatial resolution satellite data can acquire the latest earth surface data with one meter resolution in relatively short time. Ikonos satellite imagery is one of the high spatial resolution satellite imagery can be chosen and utilized as the main source for providing the surface map.